The Lady and the Indian; Representing an Inter-ethnic Marriage in Dutch and Canadian News Media (1906-1928) - Altena, Marga (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
AbstractThis essay examines how Dutch and Canadian news media represented ethnic difference through reports on the marriage of Johanna van Dommelen and Angus Montour and how the spouses influenced this news coverage (1906-1928). The analysis shows that the couple, in introducing new topics, changed the focus of reports. Articles about their marriage ended up promoting Indian activism and criticizing media representation and government policy regarding indigenous people. Johanna and Angus cleverly exploited stereotypical media representation of "Indians" to improve living conditions of the Mohawk. The mixed identity of their marriage, initially experienced as an offense to public taste, proved to be a powerful political instrument. It is a fascinating paradox that racial stereotypes in dominant media discourse provided possibilities for marginal people to express themselves publicly.